2002
DOI: 10.1128/aac.46.6.1870-1874.2002
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Randomized, Placebo-Controlled Study of Topical 5% Acyclovir-1% Hydrocortisone Cream (ME-609) for Treatment of UV Radiation-Induced Herpes Labialis

Abstract: Immunopathology is recognized as an important component of infectious disease manifestations, and corticosteroids have been used as an adjunct to antimicrobial therapy for a variety of conditions. Antiviral therapy of herpes labialis has been shown to result in only a small reduction in the time to healing and the duration of pain. To determine if topical application of a combination product containing 5% acyclovir and 1% hydrocortisone (ME-609) could provide benefit to herpes labialis patients, 380 immunocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 11 publications
2
45
0
3
Order By: Relevance
“…A meta-analysis of these studies (Evans 2002, Hull 2011 showed that treatments with Topical 5% Acyclovir-1% Hydrocortisone Cream (ME-609) has a significant positive effect on developed ulcerative lesions compared with placebo patients. (RR 0.78, 95% CI 0.70-0.85; p<0.001) (Fig.…”
Section: Acyclovir Hydrocortisone For Herpes Labialis 1417 Resultsmentioning
confidence: 99%
“…A meta-analysis of these studies (Evans 2002, Hull 2011 showed that treatments with Topical 5% Acyclovir-1% Hydrocortisone Cream (ME-609) has a significant positive effect on developed ulcerative lesions compared with placebo patients. (RR 0.78, 95% CI 0.70-0.85; p<0.001) (Fig.…”
Section: Acyclovir Hydrocortisone For Herpes Labialis 1417 Resultsmentioning
confidence: 99%
“…This led to investigations into the use of antiviral-anti-inflammatory combinations, which have been shown to be more effective than antivirals alone (18,39,40,44). Because HSL therapy, especially combination treatments, can have multiple effects-prevention of lesion progression, reduced lesion area, shorter episode duration-composite endpoints may be the most appropriate measures of their total efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the combined durations of these stages was reduced by 43% (P Ͻ 0.001) by idoxuridine among patients with ulcerative recurrences, whereas total healing time was unaffected, thereby demonstrating that antiviral treatment can reduce the duration of the most bothersome stages of HSL lesions even if total healing time is unchanged. Similar endpoints have been utilized by Evans et al (40) and Crane et al (41). However, lesion stage duration endpoints do not capture the ability of an antiviral to prevent ulcerative lesions, which may be the most important goal of HSL therapy.…”
Section: Improving Upon Traditional Measures Of Efficacy In Recurrentmentioning
confidence: 99%
See 1 more Smart Citation
“…This has consistently resulted in smaller lesions and an increase in the proportion of nonulcerative lesions, suggesting that a reduction of the inflammatory response may prevent some of the recurrences from developing into ulcerative lesions. 2,3,11 To further assess the value of combined topical steroid and antiviral therapy for HSL, the current phase III clinical trial was undertaken. We evaluated the efficacy and safety of topical ME-609, consisting of topical 5% acyclovir and 1% hydrocortisone in a proprietary cream formulation, for the treatment of recurrent HSL.…”
mentioning
confidence: 99%